O impacto do diabetes no desfecho do tratamento da tuberculose em uma regional do estado de São Paulo - Feltrin, Aline Fiori dos Santos (2015)
Introduction: Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis, better known as Koch's bacillus. It is a priority in public health in Brazil, as it is estimated that 129,000 cases occur annually in the country, which are notified only about 90,000. For the development of the disease some factors may be triggering for individuals who came into contact with the bacillus and are infected, including diabetes mellitus. Diabetes is a chronic, multi-source, weakening the immune system of individuals with the disease. As well as tuberculosis, diabetes is a public health priority. Recent studies show that diabetics are more likely to develop pulmonary tuberculosis, which can be up to four times higher than in non-diabetic subjects. Both diseases are difficult to treat and control due to side effects and life changing habits. Objective: To analyze the factors associated with the outcomes of tuberculosis treatment in diabetic and nondiabetic patients in a regional state of Sao Paulo from 1996 to 2014. Methods: Secondary data were used of tuberculosis cases reported in the information system TBWEB in the period 1996 to 2014, residents in the cities on the scope of the Regional Department of Health of São José do Rio Preto, which has 102 municipalities and a population of approximately 1,500,000 inhabitants, were excluded cases that had as outcome the change in diagnosis or patient transfer to another State, notifications without closing cases where the municipality notifying did not belong to the area, totaling 4,820 cases in the period. Bivariate analysis was performed in a model of logistic regression through the Software R, which is an open-access software for statistical analysis and graphics, considering a significance level of 5% (p <0.05) . Adjusted measurements were obtained odds ratio (OR) in order to evaluate the strength of association between independent variables and the abandonment and identify possible relationships protection risk. Results: There was a predominance of males, accounting for 72.6% and 64.4% in non-diabetics and diabetics. The age group with the highest prevalence was 20-59 years, and 78.1% in non-diabetics and 65.3% in diabetics, those with importance aged 60 and over with 34.4% of cases . Diabetes and the age of 60 years and more were presented as risk factors for dropping out, with p <0.05 and adjusted odds ratio OR = 2.8 and OR = 2.51, respectively. To death have diabetes appeared as a protective factor, with p <0.05 and OR = 0.68. Conclusion: Whereas the association tuberculosis and diabetes, major diseases and impact on public health, has been increasingly common and expected, it is essential to deepen the studies to understand the implications of comorbidity in the success or failure of treatment and evaluate the as population characteristics, regions and health care can be linked directly or indirectly in this process in order to facilitate action planning in the prevention, monitoring and treatment appropriate to this reality.